Appropriate methionine:lysine ratio for the segregated early-weaned pig - Owen, K.Q.; Richert, B.T.; Friesen, K.G.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 350 crossbred pigs (9.0 ± 2 d old and 8.4 lb +f- 2.5 BW) was used to determine the appropriate methionine: lysine ratio in diets for the segregated early-weaned pig. Two lysine levels (1.8 and 1.4%) and five methionine levels within each lysine level were used in a 2 x 5 factorial arrangement. Methionine: lysine ratios ranged from 21.5 to 33.5 %. From d 0 to 21 postweaning, all diets contained 25%dried whey, 12% lactose, 7.5% spray dried porcine plasma, 6.0% select menhaden fish meal, and 1.75% spray-dried blood meal. The basal diets containing 1.4 and 1.8% lysine were formulated to contain .301 and .387% dietary methionine, respectively. Cornstarch was replaced by Alimet(equivalent to 88 methionine) to provide the four additional experimental methionine concentrations for each lysine level. Cystine contents of all diets within each lysine level were identical at .52 and .66% for the 1.4 and 1.8% lysine diets, respectively. All other amino acids were formulated on a digestible basis to ensure that methionine was first limiting. No methionine x lysine interactions were observed throughout the 21-day experiment. Increasing dietary methionine increased average daily gain (ADG) during each week of the trial, with the maximum observed at approximately .50 and .39% methionine in the diets containing 1.8 and 1.4% dietary lysine, respectively (27.5% of lysine). Dietary methionine level had no effect on feed efficiency (F/G). Increasing dietary lysine improved ADG and F/G. In conclusion, with either dietary lysine level used, maintaining methionine at 27.5% of lysine was required to maximize growth from d 0 to 21 postweaning.
Keywords: Swine; Pigs; Growth; Methionine; Sulfur amino acids; Lysine